Community Assembly of Endophytic Fungi in Ectomycorrhizae of Betulaceae Plants at a Regional Scale - Wang, Yong-Long; Gao, Cheng; Chen, Liang; Ji, Niu-Niu; Wu, Bin-Wei; Lü, Peng-Peng; Li, Xing-Chun; Qian, Xin; Maitra, Pulak; Babalola, Busayo Joshua; Zheng, Yong; Guo, Liang-Dong (Frontiers in Microbiology, 2020)
The interaction between aboveground and belowground biotic communities drives community assembly of plants and soil microbiota. As an important component of belowground microorganisms, root-associated fungi play pivotal roles in biodiversity maintenance and community assembly of host plants. The Betulaceae plants form ectomycorrhizae with soil fungi and widely distribute in various ecosystems. However, the community assembly of endophytic fungi in ectomycorrhizae is less investigated at a large spatial scale. Here, we examined the endophytic fungal communities in ectomycorrhizae of 22 species in four genera belonging to Betulaceae in Chinese forest ecosystems, using Illumina Miseq sequencing of internal transcribed spacer 2 amplicons. The relative contribution of host phylogeny, climate and soil (environmental filtering) and geographic distance (dispersal limitation) on endophytic fungal community was disentangled. In total, 2,106 endophytic fungal operational taxonomic units (OTUs) were obtained at a 97% sequence similarity level, dominated by Leotiomycetes, Agaricomycetes, Eurotiomycetes, and Sordariomycetes. The endophytic fungal OTU richness was significantly related with host phylogeny, geographic distance, soil and climate. The endophytic fungal community composition was significantly affected by host phylogeny (19.5% of variation explained in fungal community), geographic distance (11.2%), soil (6.1%), and climate (1.4%). This finding suggests that environmental filtering by plant and abiotic variables coupled with dispersal limitation linked to geographic distance determines endophytic fungal community assembly in ectomycorrhizae of Betulaceae plants, with host phylogeny being a stronger determinant than other predictor variables at the regional scale.